Characterizing the effect of polymyxin B antibiotics to lipopolysaccharide on Escherichia coli surface using atomic force microscopy†. Issue 6 (5th January 2017) - Oh, Yoo Jin; Plochberger, Birgit; Rechberger, Markus; Hinterdorfer, Peter
Abstract: Lipopolysaccharide (LPS) on gram‐negative bacterial outer membranes is the first target for antimicrobial agents, due to their spatial proximity to outer environments of microorganisms. To develop antibacterial compounds with high specificity for LPS binding, the understanding of the molecular nature and their mode of recognition is of key importance. In this study, atomic force microscopy (AFM) and single molecular force spectroscopy were used to characterize the effects of antibiotic polymyxin B (PMB) to the bacterial membrane at the nanoscale. Isolated LPS layer and the intact bacterial membrane were examined with respect to morphological changes at different concentrations of PMB. Our results revealed that 3 hours of 10 μg/mL of PMB exposure caused the highest roughness changes on intact bacterial surfaces, arising from the direct binding of PMB to LPS on the bacterial membrane. Single molecular force spectroscopy was used to probe specific interaction forces between the isolated LPS layer and PMB coupled to the AFM tip. A short range interaction regime mediated by electrostatic forces was visible. Unbinding forces between isolated LPS and PMB were about 30 pN at a retraction velocity of 500 nm/s. We further investigated the effects of the polycationic peptide PMB on bacterial outer membranes and monitored its influences on the deterioration of the bacterial membrane structure. Polymyxin B binding led to rougher appearances and wrinkles on the outer membranes surface, which may finally lead to lethal membrane damage of bacteria. Our studies indicate the potential of AFM for applications in pathogen recognition and nano‐resolution approaches in microbiology. Abstract : The effects of antibiotic polymyxin B (PMB) to lipopolysaccharides on gram‐negative bacterial outer membranes were investigated using atomic force microscopy and single molecular force spectroscopy. Specific binding forces between lipopolysaccharides and PMB deduced energetic and kinetic parameters of the interaction. Experiments on bacterial cells revealed that PMB exposure enhances the roughness of the outer bacterial membrane, finally leading to membrane damage.